Analisis Permintaan dan Pendugaan Struktur Pasar pada Industri Jasa Laundry Kiloan di Bandar Lampung - Anggun Aprilia; Heru Wahyudi (Universitas Kristen Indonesia Toraja, 2025)
This study aims to analyze demand and market structure in Bandar Lampung's kilo laundry service industry. Focusing on identifying the relationship between price and consumer preferences on laundry demand, and determining market structure characteristics using the Herfindahl-Hirschman Index. Primary data was collected through surveys, interviews, and questionnaires from 46 kiloan laundry business owners in Labuhan Ratu District. Secondary data was obtained from literature and related institutions. Results indicate that the kilo laundry service industry in Bandar Lampung has a monopolistic competitive market structure, with a Herfindahl-Hirschman Index value of 0.0372. Price variables significantly negatively affect demand, while consumer preferences show no significant impact. Based on these findings, non-price policies such as improving service quality are recommended to enhance competitiveness and performance.